Energy generation and revenue potential from municipal solid waste using system dynamic approach. (July 2022) - Alam, Pervez; Sharholy, Mufeed; Khan, Afzal Husain; Ahmad, Kafeel; Alomayri, Thamer; Radwan, Neyara; Aziz, Abdul
Abstract: The Municipal Solid Waste (MSW) generation per capita in developing countries is generally said to grow in proportion to the gross national product. Composting and waste to energy have a brief history as management strategies for MSW in India and as alternatives to landfilling. Analysis of Energy generation and compost potential from waste can minimize the impact of MSW on the environment with the added advantage of providing a local source of energy. The study has been carried out to develop a system dynamic (SD) model to predict the energy generation, treatment, and cost analysis for MSW up to 2030. The predictive model developed in this study showed the generation rate of electrical energy potential augmented from 0 in 2001 to 58, 380 MWh in 2007 and 319, 875 MWh in 2030. Whereas, the production rate of compost reduced from 77, 000 tonnes in 2001 to 45, 000 tonnes in 2006 and then improved to 390, 000 tonnes in 2030. In addition, the predicted revenue generated from different treatment facilities increased from 0 in 2001 to Rs.335 million (4.36 million USD) in 2007 and Rs.2569 million (33.4 million USD) in 2030. As a result, revenue generated could cover the budgets required for MSW treatment and disposal services in 2030, where the required budget is negative because revenue exceeds expenditures. The developed SD model can improve a municipal solid waste management system for any City. Graphical abstract: Image 1 Highlights: SD model to predict the energy generation, treatment, and cost analysis for MSW up to 2030. In 2030, most of SW will be treated by the process of composting, biomethanation and RDF. Such models enable decision makers in prediction energy potential from MSW. Budget for MSW disposal and treatment will remain less than the capital generation by 2030. Uncollected waste is significantly reduced by the implementation of MSW treatment facilities.